Exponential Dichotomy of the Two-Dimensional Linear Differential System. (13th October 2022) - Hua, Ni; Jing, Wang; Min, Bai
Abstract :    This paper deals with a class of two-dimensional linear differential systems with periodic coefficients. A sufficient condition for the exponential dichotomy of the linear system is given by the fixed point theorem and variable substitution, and some new results are obtained.